2010
DOI: 10.1016/j.jtcvs.2010.07.086
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patients at particular risk of injury during repeat sternotomy: Analysis of 2555 cardiac reoperations

Abstract: Objectives: A variety of protective strategies during repeat sternotomy been proposed; however, it remains unclear for which patients they are warranted. Methods: We identified adults undergoing repeat median sternotomy for routine cardiac surgery at our institution between January 1, 1996, and December 31, 2007. The operative notes and perioperative outcomes were reviewed. Results: Of the 2555 patients, 1537 (60%) had undergone previous coronary artery bypass grafting, 700 (27%) previous mitral valve surgery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
111
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 15 publications
0
111
0
3
Order By: Relevance
“…Such patients are known to be associated with significantly higher mortality and morbidity, and their inclusion would have affected clinical outcomes and related complications and cost analyses. 8,9 Although specific proportions of such patients were not reported in Minutello's study, at least 19.1% of patients in the propensitymatched AVR group underwent previous coronary artery bypass graft surgery. This was significantly higher than the 5.5% reported for the unmatched raw patient data and may not be representative of the general population of patients who are considered for AVR procedures.…”
Section: Is Transcatheter Aortic Valve Implantation As Cost-effectivementioning
confidence: 89%
“…Such patients are known to be associated with significantly higher mortality and morbidity, and their inclusion would have affected clinical outcomes and related complications and cost analyses. 8,9 Although specific proportions of such patients were not reported in Minutello's study, at least 19.1% of patients in the propensitymatched AVR group underwent previous coronary artery bypass graft surgery. This was significantly higher than the 5.5% reported for the unmatched raw patient data and may not be representative of the general population of patients who are considered for AVR procedures.…”
Section: Is Transcatheter Aortic Valve Implantation As Cost-effectivementioning
confidence: 89%
“…11 The availability of miniaturized HVAD and improvement in robotic techniques has resulted in innovative techniques for LVAD placement in high-risk patients with previous median sternotomy and its associated complications. umakanthan et al 12 recently implanted an HVAD through a left thoracotomy approach with the outflow graft anastomosis performed onto the descending aorta.…”
Section: Discussionmentioning
confidence: 99%
“…6 Park et al 42 reported that when bypass graft injury occurred during repeat sternotomy, the mortality rate was 25%. Careful, directed preoperative imaging has been advocated by others as a means to reduce the frequency of injury as well as decrease operative risk in such patients.…”
Section: Frailtymentioning
confidence: 99%